The factors that influence customer satisfaction towards service quality in Tabung Haji's headquarters / Wan Lily Maznah Mahfudz Jeffry - Mahfudz Jeffry, Wan Lily Maznah (2017)
The purpose of this research to study the factors that influence customer satisfaction towards service quality in Tabung Haji's Headquarters. Basically, this study was based on the responses from customers of TH Headquarters. This research used the (SERVQUAL) dimension. There are five (5) dimensions SERVQUAL which is include tangible, reliability, responsiveness, assurances and empathy. Tabung Haji was established from the idea Royal Prof Ungku Aziz. The main function of the organizational is to save gradually to support the expenditure during pilgrimage and for another beneficial purpose, especially saving or investment. The main reasons to conduct the research are TH received several complaints on front-line service employees and counter services. Besides,some of customers aired their unsatisfied with the service quality provided in TH through the internet and social media. So,it leads to give bad impact of service quality in TH. The waiting time have lead to wasting customers time and lead to unsatisfied to counter service. So,with all these problems,the researcher conduct this study to determine the which factor of service quality give influence to customer satisfaction. Questionnaire were distribute to customer that had experience in Tabung Haji's services. The five dimension of service quality is measured using Pearson Correlation to analyze the significant of service quality towards customer satisfaction.